PEMBUATAN MINUMAN INSTAN FUNGSIONAL DARI BIOAKTIF POD HUSK KAKAO - Wasmun, Abdul Rahim, Gatot Siswo Hutomo, Herwanto (AGROTEKBIS, 2015)
This research consisted of two stages.The first stage aimed to find out the best weight of cocoa pod husk powder used in the manufacture of instant beverages of functional cocoa pod husk. The results of antioxidant capacity and total phenol analysis suggested that the use of dried cocoa pod husk with ethanol as the solvent has the highest level of both antioxidant capacity and total phenols. The second stage aimed to find out the levels of total phenols and antioxidant capacity of the instant beverages made from various extracts of cocoa pod husk. This study used a Completely Randomized design (CRD) with four levels of cocoa pod husk weight i.e. 5 g, 10 g, 15 g and 20 g as the treatments. Maltodextrin (20 g) and sucrose (10 g) were added during the process of concentrating the instant beverage. The use of 20 g cocoa pod husk resulted in highest total phenol and antioxidant capacity. Best concentration of total phenol and antioxidant are produced from 10 g cacao pod husk extract. Therefore, this extract is used as a guide in making instant drinks.